NTRM (NON TOBACCO RELATED MATERIAL) TEMBAKAU RAJANGAN MADURA PADA PETANI NON KEMITRAAN - Mustafa, Junius Velly; Tirtosastro, Samsuri; Rozana, Rozana (Universitas Tribhuwana Tunggadewi, 2018)
NTRM (Non Tobacco Related Material) is the others material beside tobacco that have big opportunity to become the dangers material source, besides distruping the production process and aesthetics. This study aims to identify the NTRM kinds on Madura cut tobacco from non-partner farmers or free farmers which has nothing to do with the company in the tobacco production process. The location of this research is in Pamekasan county madura island. Sampling in this research used non-probability sampling technique method. Selected farmers who met the criteria for planting and processing their own tobacco leave then will be sold to the free market. Farmers plan and process their own tobacco leaves in to ranjangan Madura tobacco. Selected farmers are from Galis village and Kadur village of Galis district, Asampitu village, Kretek village, and Bulai village of Pademawu district, respectively in Pamekasan regency. The result of this research in the five village showed a high NTRM content, average organic NTRM, synthetic NTRM, and non-synthetic NTRM, respectively 1,53gr/kg, 1,07gr/kg, 8,59gr/kg. The highest NTRM is non-synthetic 76,80% in the form of stone and ceramic fractions. Synthetic NTRM 9,55% especially plastic and rubber bands and Organic NTRM 13,66% like grass, banana stem, mat and mango leaves. High content NTRM tobacco ranjangan Madura especially synthetic NTRM requires attention in the guidance of free farmers especially from local government. NTRM (Non Tobacco Related Material) adalah bahan lain selain tembakau yang berpeluang besar ikut menjadi sumber bahan berbahaya, selain mengganggu proses produksi dan estetika. Penelitian ini bertujuan mengidentifikasi NTRM pada tembakau rajangan madura. Pengambilan sampel menggunakan metode non-probability sampling technique. Petani responden dipilih yang memenuhi kriteria menanam dan mengolah daun tembakaunya sendiri kemudian akan dijual ke pasar bebas. Petani menanam dan mengolah sendiri daun tembakau menjadi tembakau rajangan madura. Petani yang dipilih berasal dari Desa Galis dan Desa Kadur Kecamatan Galis, Desa Asampitu, Desa Kertek dan Desa Bulai Kecamatan Pademawu, masing-masing di Kabupaten Pamekasan. Hasil penelitian menunjukan ada kandungan NTRM yang cukup tinggi. NTRM Organik, NTRM Sintetik dan NTRM Non-Sintetik masing-masing 1,53gr/kg, 1,07gr/kg, 8,59gr/kg. NTRM paling tinggi adalah Non-Sintetik 76,80%, yang berupa batu dan pecahan keramik, NTRM Sintetik 9,55% terutama plastik dan karet gelang dan NTRM Organik 13,66% seperti rumput, pelepah pisang, tikar dan daun mangga. Tingginya kandungan NTRM tembakau rajangan madura, khususnya NTRM Sintetik, memerlukan perhatian dalam pembinaan petani bebas khususnya dari Pemerintah Daerah.